2009
DOI: 10.5210/fm.v14i9.2642
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing academic publishing online. Part II: A socio-technical vision

Abstract: Part I of this paper outlined the limitations of feudal academic knowledge exchange and predicted its decline as cross-disciplinary research expands. Part II now suggests the SOCIO-TECHNICAL DESIGN Systems theoryThe previous paper defined a knowledge exchange system (KES) as one that aims to develop, discriminate and disseminate human knowledge. An electronic KES that works across a computer network is a socio-technical system (STS) -a social system sitting on a technical base. Email is a simple example, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
(16 reference statements)
0
17
0
1
Order By: Relevance
“…Interestingly, Chang and Ley () reported that the students who preferred reading academic text from the monitor were the higher achieving students. Usually, readers indicate that they prefer the printed version of papers because of the sense of ownership provided by the printed text (Armitage et al , ; Griffith, Krampf and Palmer, ). In recent years, with the penetration of digital reading and writing technologies into higher education, submission of academic work in a digital format has become common practice in most institutions (Heider et al , ; Nelson, ; Thayer et al , ; Whitworth and Friedman, ). Consequently, students are required to submit seminar work, assignments and even examinations in digital format, and instructors are required to read, annotate and grade them in front of a digital display (Bus and Neuman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Chang and Ley () reported that the students who preferred reading academic text from the monitor were the higher achieving students. Usually, readers indicate that they prefer the printed version of papers because of the sense of ownership provided by the printed text (Armitage et al , ; Griffith, Krampf and Palmer, ). In recent years, with the penetration of digital reading and writing technologies into higher education, submission of academic work in a digital format has become common practice in most institutions (Heider et al , ; Nelson, ; Thayer et al , ; Whitworth and Friedman, ). Consequently, students are required to submit seminar work, assignments and even examinations in digital format, and instructors are required to read, annotate and grade them in front of a digital display (Bus and Neuman, ).…”
Section: Introductionmentioning
confidence: 99%
“…The academy of the future is here, as open-access transforms publishing, MOOCs transform pedagogy and academic communications become ever-increasingly digital and web-based (Cope & Phillips, 2009;Gardner & Green, 2014;Whitworth & Friedman, 2009). As academics in education, we use digital tools, such as computers and online platforms, as means to do what academics once did by hand or in person -rather than being interested in the Internet, apps, etc.…”
Section: Netiquettementioning
confidence: 99%
“…This is reflected by a number of contributions and events [9,10,18,20,21,22,23,24,25] and by the fact that Europe has lately been funding projects addressing this issue [26,27,28].…”
Section: Emerging Trends In Scientific Publicationmentioning
confidence: 99%